Systemic Lupus Erythematosus Simulating Kikuchi Fujimotos Disease: A Case Report - Islam, Mohammad Rafiqul; Manik, Abul Hayat; Jeeba, Jannat; Kasru, Mohammod Omar; Mohammed, Rakib Hasan; Amin, Md Robed (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Kikuchi Fujimotos disease (KFD) is a rare, immunemediated, self-limiting disorder with unique histopathological features. KFD is usually seen in young Asian females; however, cases have been reported throughout the world and in all ethnicities. It has been recognized that there is a rare association between Systemic Lupus Erythematosus (SLE) and KFD via sporadic case reports. The exact pathophysiological relationship between these two diseases is still unclear. We report a case of a young Asian female who presented with persistent fever followed by development of lymphadenopathy and was diagnosed as Kikuchi Fujimotos disease based on lymph node biopsy. Although an SLE workup was done and she initially did not meet the American Rheumatology Association (ARA) diagnostic criteria for lupus.The lymph node biopsy did not show typical features of SLE. At last criteria of SLE became obvious with time and case was diagnosed as SLE. J Bangladesh Coll Phys Surg 2014; 32: 231-234